Gestión y optimización del consumo de energía eléctrica residencial usando series de tiempo. - Vicente Sarango, Carlos Alfredo (2016)
The increase of the electricity demand in Ecuador is getting bigger, this effect causes a great impact on levels of voltage, current and frequency systems Generation, Transmission and Distribution, for this reason the management and estimating demand have great importance to combat this impact, with the advance of technology in power systems; the improvement of electric networks is essential, for this reason this investigation is about the management of electricity demand, prediction through time series and several proposals for optimization to minimize energy consumption in residential systems with general models applicable to improve the required result. To estimate demand using static time series forecasting is presented; all this based on a real system of consumption in a typical residence, then to optimize the energy load control, application of distributed generation and the creation of a Smart Home intelligent system to help manage the optimal resource is proposed at one time to minimize energy consumption in residence, finally as a result of this investigation wanted a reduction in the price of electricity, improvement of the reliability of distribution networks, minimize CO2 emissions, and have efficient use of energy without affecting the user comfort.